METHODS OF DEVELOPING SOCIOLINGUISTIC COMPETENCIES WITH THE PARTICIPATION OF PROVERBS AND SAYINGS - Umida Boltaboyeva Baxtiyor qizi; Abdurahim Nasirov Abdimutalipovich (Scholar Express Journal, 2023)
As you know, throughout life, a person as a social subject communicates with various, often intersecting social groups, the number of which is constantly increasing. All of them together affect the personality of the individual. Within the framework of the intercultural approach, the main task of language education is the positive development of the individual and his self-awareness because of acquiring new linguistic and cultural experience. The experience of teaching foreign languages shows that tofulfill communicative tasks, a student who speaks a language uses his general abilities in combination with his own language competence, which includes both linguistic and pragmatic, and sociolinguistic competence. Sociolinguistic competence includes the knowledge and skills necessary for the effective use of language in a social context. Each nation has its own proverbs, sayings, proverbs, fairy tales, epics, epics, that is, everything that makes up oral folk art and determines the distinctive features of concept spheres in different cultures. The analysis of English proverbs allows us to identify similarities and differences in proverbial concepts when they are compared
Keywords: linguistic and cultural experience; communication skills; sociolinguistic and pragmatic competencies; language barrier